FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN BUDAYA KESELAMATAN PASIEN (PATIENT SAFETY CULTURE) PADA PERAWAT DI RAWAT INAP RSU KABUPATEN TANGERANG - ida faridah; rizki isphani; euis laela badriah (Universitas Yatsi Madani, 2019)
Background: Patient safety is important, if event of infection in hospital patients will have a detrimental impact on the hospital, staff and on the patient especially as the recipient of the service. The other impact caused is the decreasing level of public confidence in the health services provided. Therefore the application of patient safety should be a culture. Objective: To identify factors influencing the implementation of patient safety culture by nurses at the ward of Tangerang General Hospital. Research Method: Correlative descriptive research with cross sectional approach. Population in this research is all nurse at ward of Tangerang General Hospital in 2018 as many as 205. Sample counted 68 nurses taken with systematic random sampling technique. Data obtained by distributing questionnaires that have been valid and reliable. Univariate and bivariate data analysis using chi-square test. Result of research: Of 68 nurses most of which were 35 nurses (51,5%) were having good application of patient's culture of awareness, have knowledge of applying good patient safety culture that were 41 nurses (60,3%), have high motivation about cultural application patient safety were 39 nurses (57,4%), expressed effective leadership support that were 37 nurses (54,4%). There was an influence between nurse knowledge level and patient safety culture with pvalue = 0,007 and POR = 4,580 (95% CI = 1,605-13,067). There was an influence between nurse motivation and patient safety culture with pvalue 0,002 and POR = 5,906 (95% CI = 2,044-17,063). There was an influence of leadership support with application of patient safety culture with pvalue 0,028 and POR = 3,357 (95% CI = 1,237-9,110). Conclusions and Suggestions: There is an influence of knowledge, motivation and leadership support with the application of the patient's safety culture by nurses in the ward. Hospitals are advised to improve the implementation of existing patient safety so that it becomes a culture.